2016
DOI: 10.1177/1556264616633963
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consent for HIV Prevention Research Involving Sexual and Gender Minority Youth

Abstract: This project examined the attitudes of sexual and gender minority youth (SGMY) toward guardian permission for a pre-exposure prophylaxis (PrEP) adherence trial and their preparedness to provide informed, rational and voluntary self-consent. Sixty sexually active SGMY (ages 14–17) participated in online survey and asynchronous focus group questions after watching a video describing a PrEP adherence study. Youth responses highlighted guardian permission as a significant barrier to research participation, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
85
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 52 publications
(80 reference statements)
9
85
0
6
Order By: Relevance
“…The present study thus joins others in highlighting how well-intentioned IRBs that do not apply federal regulations permitting the waiver of guardian permission for sexual health research may contribute to the persistence of health disparities and undermine sexual and transgender minority youth's right to evidence-based interventions essential to their health and wellbeing (Fisher et al, 2016; Fisher et al, 2013; Fisher & Mustanski, 2014; Mustanski & Fisher, 2016). To remedy this situation, investigators can partner with their IRBs in developing materials that enhance youth's ability to give informed and voluntary consent through age appropriate informational materials (Fisher et al, 2016; Ott et al, 2013) and materials that provide transgender appropriate and informative information about levels of risk for HIV given one's gender identity, sexual orientation and risk practices to enable youth to accurately estimate their own risks for invention.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The present study thus joins others in highlighting how well-intentioned IRBs that do not apply federal regulations permitting the waiver of guardian permission for sexual health research may contribute to the persistence of health disparities and undermine sexual and transgender minority youth's right to evidence-based interventions essential to their health and wellbeing (Fisher et al, 2016; Fisher et al, 2013; Fisher & Mustanski, 2014; Mustanski & Fisher, 2016). To remedy this situation, investigators can partner with their IRBs in developing materials that enhance youth's ability to give informed and voluntary consent through age appropriate informational materials (Fisher et al, 2016; Ott et al, 2013) and materials that provide transgender appropriate and informative information about levels of risk for HIV given one's gender identity, sexual orientation and risk practices to enable youth to accurately estimate their own risks for invention.…”
Section: Discussionmentioning
confidence: 54%
“…Despite the fact that a majority of 14 – 17 year olds reported disclosure and at least some family acceptance, approximately half reported they would be unlikely to participate if guardian permission was required. Fear of being stigmatized, punished, or in some cases, victimized by their families if guardian permission results in disclosure of their sexual orientation or gender identity has been identified as a barrier to participation among lesbian, gay and bisexual youth (D'Amico & Julien, 2012; DiClemente, Sales, & Borek, 2010; Fisher et al, 2016; Gilbert et al, 2015; Macapagal, Coventry, Arbeit, Fisher, & Mustanksi, 2016; Mustanski, 2011; Mustanski et al, in press). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors suggested that parental monitoring may increase risk because, in the context of YMSM trying to maintain secrecy, it might be more difficult to plan for sex and thereby obtain and use condoms consistently 38 . Qualitative research with sexual and gender minority adolescents has found that many parents enforce a code of silence about sex, which may hamper their ability to monitor their children’s risk behaviors 39 . In terms of substance use, Bouris and colleagues 21 identified five articles in their review.…”
mentioning
confidence: 99%